Deletion of mitochondrial DNA in a case of early-onset diabetes mellitus, optic atrophy, and deafness (Wolfram syndrome, MIM 222300). - Rötig, A (1993)
The Wolfram syndrome (MIM 222300) is a disease of unknown origin consisting of diabetes insipidus, diabetes mellitus, optic atrophy, and deafness. Here we report on a generalized deficiency of the mitochondrial respiratory enzyme activities in skeletal muscle and lymphocyte homogenate of a girl suffering from the Wolfram syndrome. In addition, we provide evidence for a 7.6-kilobase pair heteroplasmic deletion (spanning nucleotides 6465-14135) of the mitochondrial DNA in the two tissues and show that directly repeated sequences (11 bp) were present in the wild-type mitochondrial genome at the boundaries of the deletion. Neither of the patient's parents was found to bear rearranged molecules. This study supports the view that a respiratory chain defect can present with insulin-dependent diabetes mellitus as the onset symptom. It also suggests that a defect of oxidative phosphorylation should be considered when investigating other cases of Wolfram syndrome, especially because this syndrome fulfills the criteria for a genetic defect of the mitochondrial energy supply: (a) an unexplained association of symptoms (b) with early onset and rapidly progressive course, (c) involving seemingly unrelated organs and tissues.